Toward the improvement of teaching in object-oriented programming: the integration of intelligent chatbot assistance and professor Alex's implementation - Henriquez Miranda, Carlos; Rios Perez, Jesus David; Sanchez-Torres, German (REVISTA COLOMBIANA DE TECNOLOGIAS DE AVANZADA (RCTA), 2024)
In education, chatbots provide personalized learning, instant feedback, and accessible support, enhancing student engagement and understanding across various academic subjects. This study investigates the deployment of a chatbot on the SnatchBot platform, integrated with Telegram, to assist university students in Object-Oriented Programming (OOP). The development of the chatbot included defining objectives, designing its personality, selecting tools, and creating a conversation flow using natural language processing (NLP). Assessed through surveys, the chatbot, named Profe Alex, significantly enhanced student autonomy in OOP by providing concepts, quizzes, and code examples. A survey revealed that 90% of the users positively rated the tool, confirming its effectiveness in OOP instruction. The findings indicate substantial potential for chatbots as educational tools in computer science and point towards a broader application of AI in education.